Associations of Thyroid Hormones Profile During Normal Pregnancy and Postpartum With Anxiety, Depression, and Obsessive/Compulsive Disorder Scores in Euthyroid Women - Konstantakou, Panagiota; Chalarakis, Nikos; Valsamakis, Georgios; Sakkas, Evangelos Grigoriou; Vousoura, Eleni; Gryparis, Alexandros; Sakkas, Grigorios Evangelou; Papadimitriou, George; Zervas, Ioannis; Mastorakos, George (Frontiers in Neuroscience, 2021)
Objective: Thyroid dysfunction (overt and subclinical) has been consistently linked to pregnancy adversity, abnormal fetal growth and development. Mood disorders such as anxiety, depression and obsessive-compulsive disorder (OCD) are frequently diagnosed during pregnancy and at postpartum and emerging evidence suggests association with impaired offspring neurodevelopment and growth. This study aimed to examine potential associations between thyroid function and mood disorders during pregnancy and postpartum. Design: Prospective study, measuring thyroid hormones and assessing mood disorders by employing specific questionnaires in the same cohort of 93 healthy pregnant women at the 24th (2nd trimester) and 36th (3rd trimester) gestational weeks and at the 1st postpartum week. Methods: Serum thyroid hormones, TSH, anti-TPO, and anti-Tg antibodies were measured at the 24th (2nd trimester) and 36th (3rd trimester) gestational weeks and at the 1st postpartum week. Specific validated questionnaires were employed at the same time-points to assess separately anxiety (GADI, PENN, STAI-S, STAI-T), depression (EPDS, BLUES, BDI) and obsessive compulsive disorder (OCD) (Y-BOCS). Results: At the 2nd trimester, FT3 and TSH concentrations correlated negatively (p<0.010, r= -0.545) and positively (p<0.050, r=0.837) with GADI score, respectively; FT4 concentrations correlated negatively with GADI (p<0.010, r=-0.768), PENN (p<0.010, r=-0.384), EPDS (p<0.050, r=-0.364) and Y-BOCS (p<0.010, r=-0.544) scores. At the 3rd trimester, rT3 concentrations correlated positively with BLUES score (p=0.00, r=0.89); FT4 concentrations correlated negatively with GADI (p=0.001, r=- 0.468), EPDS (p=0.036, r= -0.39) and Y-BOCS scores (p=0.001, r= -0.625); TSH concentrations correlated positively with GADI (p= 0.015, r=0.435), STAI-S (p= 0.024, r= 0.409) and Y-BOCS (p= 0.041, r= 0.389) scores. At postpartum, rT3 concentrations correlated positively with PENN (p=0.024, r= 0.478), STAI-T (p= 0.014, r= 0.527), EPDS (p=0.046, r= 0.44), and BDI (p= 0.021, r= 0.556) scores; TSH and anti-TPO antibodies concentrations correlated positively with Y-BOCS score (p=0.045, r= 0.43) and BLUES score (p=0.070, r= 0.586), respectively.